American Government, Second Edition - Mirya Holman (University Press of Florida, 2018)
This exciting new book explores the role of government, politics, and policy in American lives. Full of real life applications and scenarios, this text encourages and enables political thinking. The second edition has been updated to include recent developments in U.S. politics and government. This includes the description and analysis of the 2016 elections as well as the early Trump administration. Chapters have expanded coverage of immigration policy, environmental policy, economic policy, and global affairs (including counterterrorism policy). The text also includes analysis of racial issues in contemporary American politics and law. It also addresses questions about the state of the economy, jobs, and wages.